Effect of the Dielectric Barrier Discharge Plasma on the Optical Properties of SnO2 Thin Film. - Murbat, Hamid H; Al-Ansari, Ramiz Ahmad; Brrd, Alaa Khamees (Al-Nahrain Journal of Science, 2018)
In this paper, a dielectric barrier discharge DBD plasma system was used to study effects of the nonthermal plasma on the optical properties of the tin oxide (SnO2) thin films. tin oxide (SnO2) thin were deposed on cleaned glass substrates at 450˚C using spray pyrolysis deposition technique prepared from SnCl4:5H2O solution with concentration (0.1M).The prepared films were exposure to different time intervals (0,2,4,6,8 and 10)min.UV-VIS spectra of the films were studies using optical absorbance measurements which were taken in the spectral region from 190nm to 1100nm. The transmittance and reflectance spectra of the films in the UV-VIS region were also studied.The transmittance T, the Reflectance R, absorption coefficient α, energy gap Eg, extinction coefficient K, refractive index n, dielectric constant ϵ and optical conductivity were studied. It is found that the Reflectance, absorption coefficient, extinction coefficient and optical conductivity were increased with exposure time and the transmittance, energy gap, refractive index, dielectric constant were decreased with exposure time of DBD plasma.